Menu card from the Gopal Krishna Terekar Mahila Food Festival - Mumbai Archive Project Team (Jio Institute, 2024)
The menu card from the Gopal Krishna Terekar Mahila Food Festival showcases the culinary heritage of the Koli community from Versova.